Rearrangement of Multiferroic BiFeO3 Nanodots Smaller than 15 nm Using Atomic Force Microscopy. Issue 2 (10th December 2013) - Meang, Wan J.; Son, Jong Y.; Paranthaman, P.
<x xml:space="preserve">Abstract</x> In this study, we demonstrate an atomic force microscopy process for manipulating multiferroic BiFeO3 nanodots smaller than 15 nm to desired positions on a Nb‐doped SrTiO3 substrate. For formation of the BiFeO3 nanodot array, nanocrystal movement was achieved using a +1.2 V biased conducting atomic force microscopy (CAFM) followed by nanocrystal attachment to the tip. Using this method, high‐density BiFeO3 nanodot arrays with a density greater than 0.5 Tb/in.2 can be achieved. Perfectly flipped ferroelectric polarization with an external electric field was observed for each BiFeO3 nanodot, whose ferroelectric properties were confirmed using piezoelectric force microscopy.